Gas-sensing properties of zinc ferrite nanoparticles synthesized by the molten-salt route - Darshane, Sonali L.; Deshmukh, Rupali G.; Suryavanshi, Shankar S.; Mulla, Imtiaz S. (Journal of the American Ceramic Society, 2008)
Zinc ferrite (ZnFe2O4) nanoparticles have been synthesized at 700 degrees C using sodium chloride as a growth inhibitor. Single-phase formation of spinel zinc ferrite having crystallite size in the range of 15-20 nm was observed by XRD and confirmed by TEM. In the present work, the gas-sensing properties of these zinc ferrite nanoparticles toward ethanol, LPG, H-2, NOx. SOx, and H2S have been studied. It was found that they exhibit excellent selective sensitivity toward 200 ppm of H2S at the operating temperature of 250 degrees C, and thus this nanosized ferrite is expected to be useful in an industrial application as a potential H2S gas sensor.